1995
DOI: 10.1128/aac.39.5.1054
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical corrections for bacterial loss in pharmacodynamic in vitro dilution models

Abstract: In vitro dilution models are used to simulate in vivo drug concentration-time profiles and thus to study the effects of various antibiotic concentrations on the bacteria investigated. The major disadvantage of these models is permanent dilution of the bacterial culture, which falsifies the resulting kill curves. Known equations, which usually correct bacterial loss by simple first-order kinetics, do not take into account special test conditions, such as variable elimination rate constants, exceptionally long p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 10 publications
0
23
0
Order By: Relevance
“…This effect is particularly important when the dilution rate is higher than the bacterial growth rate, and the resulting increased bacterial clearance needs to be accounted for. Some equations to correct this effect for exponentially changing cultures have been proposed (117,64). Löwdin et al employed a 0.45-m filter membrane in the culture flask to prevent bacterial outflow.…”
Section: Models With Variable Antibiotic Concentrationsmentioning
confidence: 99%
“…This effect is particularly important when the dilution rate is higher than the bacterial growth rate, and the resulting increased bacterial clearance needs to be accounted for. Some equations to correct this effect for exponentially changing cultures have been proposed (117,64). Löwdin et al employed a 0.45-m filter membrane in the culture flask to prevent bacterial outflow.…”
Section: Models With Variable Antibiotic Concentrationsmentioning
confidence: 99%
“…If the rate of reduction was less than that which would have been predicted by flow rate alone, the reduction was attributed to the effect of the drug. However, if the reduction in the numbers of CFU was greater than or equal to that predicted by the flow rate, a mathematical model that allowed correction for this dilutional effect was used (11). The changes in the log number of CFU per milliliter from the starting inocula at times of 24 and 48 h were determined for each regimen and isolate.…”
Section: Antimicrobialmentioning
confidence: 99%
“…Moreover, prior studies demonstrated that this inoculum reproducibly infects sterile SEVs in this model (12). A peristaltic pump supplied fresh MEM and removed exhausted medium from the model at a half-life equal to 6 h. At this flow rate, loss of S. aureus from the model is negligible, since the doubling time (ϳ20 min) far exceeds the loss attributed to model effluent (10). A magnetic stir bar continuously circulated the fluid within the chamber compartment of the model.…”
Section: In Vitro Model Of Ie (12)mentioning
confidence: 99%
“…Furthermore, tPMP-1-resistant S. aureus or C. albicans strains cause significantly more severe forms of experimental IE than do tPMP-1-susceptible counterpart strains (3,11,29). In addition, the enhancement of the antimicrobial activities of conventional antibiotics by tPMPs in vitro was previously demonstrated (8)(9)(10).…”
mentioning
confidence: 99%